THE PORTRAYAL OF NATIONAL SPACE THROUGH TOPONYMS IN O‘TKIR HOSHIMOV’S NOVELLA THE AFFAIRS OF THE WORLD (DUNYONING ISHLARI) - S.B.Khursankulov; D.Z.Abduazimova (TADQIQOTLAR, 2026)
Abstract. This article examines the artistic-aesthetic and linguopoetic features of toponyms used in O‘tkir Hoshimov’s novella The Affairs of the World (Dunyoning ishlari). The study analyzes the semantic content of place names in the work, their role in constructing the concept of national space, and their functions in reflecting the worldview of the characters as well as the cultural memory of the people. The findings demonstrate that toponyms in the literary text serve not only as indicators of location but also as significant poetic units that convey national identity, spiritual values, and ethnocultural perceptions.